Answer:
The expression (-root3·a - a)², can be simplified into the form a² × (4 + 2·√3)
Explanation:
The given expression can be written as follows;
(-root3·a - a)² = (-√3·a - a)²
Which can be expanded to give;
(-√3·a - a) × (-√3·a - a) = 3·a² + 2·√3·a² +a²
We collect like terms to get;
3·a² + 2·√3·a² +a² = 3·a² +a²+ 2·√3·a² = 4·a² + 2·√3·a²
We factorize out the common coefficients of the terms to have;
4·a² + 2·√3·a² = a² × (4 + 2·√3)
Which gives the initial expression (-root3·a - a)², to presented in the form a² × (4 + 2·√3).